The Influence of Packaging and Price on Consumer Buying Interest in Contemporary Beverage Products through Attitude as a Variable - Fadin, Fadin Nur Rachman (Jurnal Economic Resource, 2024)
This study aims to determine the effect of packaging and price on consumer buying interest in the latest beverage products through attitudes as an intervening in Xiboba Kta Madiun products. This type of research is descriptive quantitative. Data collection is carried out by distributing questionnaires. The sampling method used is the purposive sampling method. The sample in this study is people in Madiun City. The data used in the study are primary data. Related data analysis using Causality analysis with SEM PLS with the help of SmartPLS 3.0 program. The results showed that packaging had a positive and significant effect on the interest in buying Xiboba Products. If the packaging is considered better, it will increase consumer buying interest. The results showed that price had a positive and significant effect on the buying interest of Xiboba Products. If prices are more competitive or competitive, it will increase consumer buying interest. The results showed that packaging had a positive and significant effect on the attitude of consumers of Xiboba Products. If the packaging is considered better, consumer attitudes tend to be better. The results showed that price had a positive and significant effect on consumer attitudes of Xiboba Products. If prices are more competitive or competitive, consumer attitudes tend to be better. The results showed that attitude had a positive and significant effect on the interest in buying Xiboba Products. If consumer attitudes towards products are getting better, it will increase consumer buying interest.